2018
DOI: 10.1051/0004-6361/201832582
|View full text |Cite
|
Sign up to set email alerts
|

Feedback from reorienting AGN jets

Abstract: Aims. We test the effects of re-orienting jets from an active galactic nucleus (AGN) on the intracluster medium in a galaxy cluster environment with short central cooling time. We investigate both the appearance and the properties of the resulting cavities, and the efficiency of the jets in providing near-isotropic heating to the cooling cluster core. Methods. We use numerical simulations to explore four models of AGN jets over several active/inactive cycles. We keep the jet power and duration fixed across the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 119 publications
6
47
0
Order By: Relevance
“…We find a qualitatively similar result that even our most widely precessing jets boost the turbulence at a large radius at most by a factor of 2, insufficient to quench on its own (Paper II). We also found that a more widely precessing jet can heat the core region up more, consistent with the widely re-oriented jet in Cielo et al (2018).…”
Section: Comparison With Other Simulationssupporting
confidence: 82%
“…We find a qualitatively similar result that even our most widely precessing jets boost the turbulence at a large radius at most by a factor of 2, insufficient to quench on its own (Paper II). We also found that a more widely precessing jet can heat the core region up more, consistent with the widely re-oriented jet in Cielo et al (2018).…”
Section: Comparison With Other Simulationssupporting
confidence: 82%
“…Nonetheless, narrow outflows have their own challenges, which become apparent through running idealized simulations. Firstly, as shown by Vernaleo & Reynolds (2006) and confirmed by Cielo et al (2018), jets that fire in a fixed direction tend to deposit their energy at increasing larger distances and ultimately, end up doing so beyond the group/cluster core. As a result, such jets only delay the onset of catastrophic cooling, not prevent it.…”
mentioning
confidence: 90%
“…Alternatively, reorienting jets similar to the case of NGC 5044 (see Figure 8) may provide an alternative way of heating the gas in a quasi-isotropic way. Cielo et al [277] presented simulations of AGN/IGrM interaction in the case of precessing jets and claimed that the distributed energy is sufficient for offsetting cooling and reproducing the features seen in real cool-core clusters. 17)) into its main positive/negative components: compressions/rarefactions (second panel), stretching/squeezing motions (third), baroclinicity (fourth)-adapted from Wittor and Gaspari [239].…”
Section: Agn Feedback and Heating Processesmentioning
confidence: 99%